Analysis of Requirements Phase as a Step for Software Engineering Automation - Abdul M. Khidhir; Noor Shihab (Al-Rafidain Journal of Computer Sciences and Mathematics)
Requirements engineering is the first phase of the software engineering process. This phase is the basis of other phases, so it is a very critical phase. Incomplete, ambiguous and misunderstanding requirements lead to fail in the product. For this reason, attention must be increased in requirements engineering  to obtain accurate, complete and unambiguous requirements to satisfy users' needs in their products. In this paper, an attempt to analyze the requirement phase and produce analysis model is presented by using EA (Enterprise Architect) tool to offer a smart support for requirements engineering processes and introducing them as basis in requirements development in software engineering automation.